Dangerous Gifts Gender and Exchange in Ancient Greece - Lyons, Deborah (University of Texas Press, 2021)
Deianeira sends her husband Herakles a poisoned robe. Eriphyle trades the life of her husband Amphiaraos for a golden necklace. Atreus's wife Aerope gives away the token of his sovereignty, a lamb with a golden fleece, to his brother Thyestes, who has seduced her. Gifts and exchanges always involve a certain risk in any culture, but in the ancient Greek imagination, women and gifts appear to be a particularly deadly combination. This book explores the role of gender in exchange as represented in ancient Greek culture, including Homeric epic and tragedy, non-literary texts, and iconographic and historical evidence of various kinds. Using extensive insights from anthropological work on marriage, kinship, and exchange, as well as ethnographic parallels from other traditional societies, Deborah Lyons probes the gendered division of labor among both gods and mortals, the role of marriage (and its failure) in transforming women from objects to agents of exchange, the equivocal nature of women as exchange-partners, and the importance of the sister-brother bond in understanding the economic and social place of women in ancient Greece. Her findings not only enlarge our understanding of social attitudes and practices in Greek antiquity but also demonstrate the applicability of ethnographic techniques and anthropological theory to the study of ancient societies